Rb-Sr Age of the Late-Kinematic Phase of the Hudsonian Orogeny in the Beaverlodge Area, Saskatchewan - Sassano, G. P.; Baadsgaard, H.; Burwash, R. A. (Canadian Journal of Earth Sciences, 1974)
The Tazin Complex, north of Lake Athabasca, shows widespread development of mylonites associated with northeast trending faults. Hudsonian metamorphism has caused recrystallization of cataclastic rocks with post-crystalline deformation forming narrow zones of later mylonites. Syenitic lamprophyre dikes which, with very few exceptions, are undeformed, form the latest intrusive rocks in the area, filling dilatant fractures developed during crustal uplift.Rb–Sr whole rock dating of eight samples of the dikes in the Beaverlodge area, yield an isochron of 1779 ± 72 m.y. (initial ratio = 0.709 ± 0.001, MSWD = 0.39, λ( 87 Rb) = 1.39 × 10 −11 /yr). The late-kinematic phase of the Hudsonian orogeny, therefore, occurred around 1780 m.y. ago, at which time the uplift of the northwestern sector of the Churchill structural province look place. It is also believed that the date is close to the time of final movement of the St. Louis Fault.